The influence of entrepreneurs’ mental models on organizational absorptive capacity: a multilevel perspective - Hermes, Lisiane Caroline Rodrigues; Sausen, Jorge Oneide; Ferreira, Gloria Charão; Rossetto, Carlos Ricardo (Revista de Administração da UFSM, 2023)
Purpose: Entrepreneurs have cognitive styles that directly determine organizational behavior. When building their mental models, the entrepreneur uses both individual and collective capacities, which, in turn, mediate the performance of an organization, configuring themselves in a multilevel perspective. This article aims to analyze the effect of entrepreneurs’ mental models on absorptive capacity in incubated companies. Design/methodology/approach: This article is based on descriptive research with a quantitative approach to the data. A closed questionnaire was applied to 132 incubated companies belonging to the Consortium of Community Universities of Rio Grande do Sul (Consórcio de Universidades Comunitárias do Rio Grande do Sul - Comung) and Santa Catarina Association of Educational Foundations (Associação Catarinense das Fundações Educacionais - Acafe). The statistical treatment used to analyze the relationships investigated in this research comprised descriptive statistical analysis and Modeling by Structural Equations (SEM), with the help of SPSS® version 2.2 and SmartPLS® version 3.2.8 software. Findings: The results showed a positive relationship between the cognitive variables of the entrepreneurs’ mental models in the organizational Absorptive Capacity (ACAP). It is possible to infer that these are significant predictors of the development of organizational ACAP in the companies that make up this sample. This study presents a set of mental models’ cognitive variables related to organizational ACAP. Originality/value: We suggest a qualitative approach that can deepen the observations regarding the relationships investigated in this study. Such an approach would help understand how the relationship between the cognitive variables of the mental models of entrepreneurs in organizational ACAP occurs.